Energy-efficient building design in tropical climates: A systematic literature review of heat transfer strategies (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Architectural structures located in tropical regions are exposed to substantial energy demands for cooling through air-conditioning systems due to intense solar radiation and persistently high humidity levels. Consequently, these regions are characterized by high energy consumption, where cooling loads are dominant, thereby making the role of heat-transfer mechanisms and effective architectural design increasingly critical for achieving thermal comfort and energy efficiency, particularly when compared with middle-latitude regions. The primary objective of this study is to synthesize contemporary research addressing heat-transfer control strategies in energy-efficient building design for tropical climates. The review employs the PRISMA methodological framework, systematically examining 85 peer-reviewed articles published between 2010 and 2025 and indexed in major scientific databases. The analyzed studies are categorized according to the design strategies adopted, including passive cooling approaches, building-envelope optimization, material innovation, and the use of simulation tools in architectural design. The findings indicate that passive strategies, particularly natural ventilation, shading through overhang devices, and the application of reflective or high-albedo surface materials, exhibit the highest effectiveness in mitigating heat gain. Furthermore, the use of advanced insulation materials and adaptive façade systems demonstrates significant potential for enhancing building performance in future applications. However, the integration of simulation-based design methods with empirical validation remains at an early stage of development. Overall, this paper provides a comprehensive analysis of prevailing research trends, while critically addressing current challenges and outlining future prospects for sustainable cooling strategies within the tropical built environment.
Keywords: Energy saving design; Tropical climate; Heat flow; Passive cooling